DISTINCT CELLULAR MIGRATION INDUCED BY Leishmania infantum chagasi AND SALIVA FROM Lutzomyia longipalpis IN A HEMORRHAGIC POOL MODEL - Vasconcelos, Camila Oliveira; Coelho, Zirlane C. Branco; Chaves, Cristina de Souza; Teixeira, Clarissa Romero; Pompeu, Margarida M. Lima; Teixeira, Maria Jania (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Recruitment of a specific cell population after Leishmania infection can influence the outcome of the disease. Cellular migration in response to Leishmania or vector saliva has been reported in air pouch model, however, cellular migration induced by Leishmania associated with host's blood and vector saliva in this model has not been described. Herein we investigated cellular migration into air pouch of hamster after stimulation with combination of L. chagasi and host's blood and Lutzomyia longipalpis saliva. Migration induced by saliva was 3-fold more than those induced by L. chagasi alone. Additionally, L. chagasi associated with blood and saliva induced significantly even more leukocytes into air pouch than Leishmania alone. L. chagasi recruited a diverse cell population; however, most of these cells seem to have not migrated to the inflammatory exudate, remaining in the pouch lining tissue. These results indicate that L. chagasi can reduce leukocyte accumulation to the initial site of infection, and when associated with vector saliva in the presence of blood components, increase the influx of more neutrophils than macrophages, suggesting that the parasite has developed a strategy to minimize the initial inflammatory response, allowing an unlimited progression within the host. This work reinforces the importance of studies on the salivary components of sand fly vectors of leishmaniasis in the transmission process and the establishment of the infection.